Exploring skills acquisition differences in leather work among technical university students in Ghana: The case of Tamale Technical University - Mohammed Seini Issah; Essel Harry Barton; Akosua Tachie-Menson (Universitas Muhammadiyah Malang, 2024)
This research examines gender-based differences in skills acquisition among students, with a particular emphasis on Creativity. Utilizing an independent sample t-test, the study evaluated the development of creative skills among male and female students in Leatherwork, specifically focusing on Decorative Techniques and Thonging Techniques. The data were derived from a cohort of students enrolled in Leatherwork training from level 100 to level 300 of the Higher National Diploma (HND) program at the Tamale Technical University. The analysis aimed to determine whether significant differences exist in the way male and female students acquire Creative Skills in Leatherwork. Factors such as instructional methods and gender-specific learning preferences were explored. The results of the independent sampled t-test indicated that there were no notable disparities in creativity scores between male and female students within the pedagogical framework adopted. The findings further suggested that there were no significant differences in skill acquisition in Leatherwork between males and females. The study demonstrates that the pedagogical framework accommodates the skills development and acquisition of both genders, highlighting the need for educational strategies that address these differences and promote the development of creativity equally among all students, irrespective of gender. Implications for curriculum design and gender-sensitive pedagogy were discussed to foster more equitable learning outcomes.